(untitled) (KONFERENSIYA, 2025)
Critical Thinking (CT) has been increasingly recognized as a vital skill for students, serving as a key indicator of the quality of their learning. To cultivate effective critical thinkers, it is essential to integrate CT into the curriculum and teaching methods across all grade levels. This research presents a systematic review of existing literature on the instruction of CT skills, culminating in a conceptual framework that outlines four primary debates among researchers in the field. One significant debate centers on whether technology can enhance students’ CT skills. The findings from current practices suggest that teaching methods often prioritize subject matter over the development of CT. This indicates a notable gap in the instruction of CT skills, particularly regarding innovative teaching strategies and the incorporation of new technologies. Furthermore, the research underscores the necessity for additional studies aimed at exploring novel approaches to teaching CT skills effectively. In summary, while there is a growing recognition of the importance of CT in education, there remains a critical need for more innovative and technologydriven methods to effectively teach these skills in the classroom